DESCRIPCION DEL CRANEO Y MANDIBULA DE UN NUEVO EJEMPLAR DE SCELIDOTHERIUM SP. (Ameghiniana, 2013)
In this work, the authors describe a skull and jaw of Scelidotherium sp.; it was found in sediments presumably of Middle Pleistocene (Ensenadan age ), From Ge- neral La Madrid, Provincia de Buenos Aires, Argentina.